Are visiting oncologists enough? A qualitative study of the needs of Australian rural and regional cancer patients, carers and health professionals. Issue 3 (18th September 2012) - Grimison, Peter; Phillips, Fiona; Butow, Phyllis; White, Kate; Yip, Desmond; Sardelic, Frank; Underhill, Craig; Tse, Regina; Simes, Robyn; Turley, Kim; Raymond, Carmel; Goldstein, David
Abstract Aim Survival rates for patients with cancer who live in rural and regional areas are worse than in metropolitan areas. This may be due to geographical isolation, delayed diagnosis, inadequate transport, lower socioeconomic status and workforce shortages. We conducted a qualitative study of rural patients, carers and health professionals. It aimed to identify concerns about, and strategies to optimize cancer care from those with direct experience. Methods Focus groups and structured interviews were conducted in New South Wales, Australia at four rural and regional hospitals (Bega, Dubbo, Tamworth and Albury) and three metropolitan locations (in Sydney and the Jean Colvin Hostel) caring for rural patients. Sessions were audiotaped, transcribed and analyzed using thematic analysis. Results In total, 36 patients, 14 carers and 32 health professionals were interviewed in seven focus groups and 42 individual interviews. Concerns related to access to oncologists and other health professionals, and for services for investigation and treatment, the financial and social consequences of travel, unmet carer support needs and the hardships for health professionals. Strategies for improvement included comprehensive staffing and services coordinated in a hub and spoke model from adjacent larger centers, adequate reimbursement for travel and better carer support. Conclusion We identified broad concerns about regional and rural cancer care in Australia. The Australian Federal Government commitment of 560 million to establish regional cancer centers is welcome; however, improvements must extend beyond infrastructure funding in large regional centers to comprehensive staffing in centers currently lacking resident oncologists, travel support and assistance for carers.